Biomechanical evaluation of a novel correction technique for adolescent idiopathic scoliosis: finite element analysis - Shi, Anli; Ma, Rong; Wang, Zhiqiang; Liu, Xiaoyin; Zhang, Jianqun; Ge, Zhaohui (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeTo introduce a novel surgical technique, the Simultaneous Double-Rod Reverse Derotation (SDRRD), and to compare its corrective outcomes and biomechanical performance with traditional surgery using finite element analysis.Materials and methodsThree finite element models, including the single-rod fixed pedicle screw model (M1), the double-rod polyaxial pedicle screw model (M2), and the double-rod monoplane pedicle screw model (M3) were constructed using CT data from a Lenke 1 C N adolescent idiopathic scoliosis patient. The rod rotation technique was applied in M1 and M2, while the SDRRD technique was implemented in M3. The surgical outcomes in three dimensions and the biomechanical outcomes in the spine and implants were investigated following the simulation of the corrective process.ResultRegarding correction efficacy, M2 and M3 overmatched M1 in the coronal and sagittal planes, while M3 achieved superior axial rotation correction compared to M1 and M2. The stress on the apical vertebra is most considerable, while that on the lower instrumented vertebra is lowest in the vertebrae and intervertebral discs across M1 to M3. A considerable stress reduction is observed from M1 to M3 in most regions, with the highest stress in M1 and the lowest in M3. There is no considerable difference in the maximum stress of the implants among the three groups.ConclusionThe SDRRD technique yields favourable outcomes in coronal and sagittal plane correction, particularly in reducing axial rotation. Moreover, SDRRD effectively minimizes the stress experienced by the vertebrae and intervertebral discs.